Effect of Antioxidants on the Occurrence of Pre-eclampsia in Women at Increased Risk - Sultan, Mahmoud; Salim, Hassan; El Maslawy, Yahya; Al-Tamimi, Ibrahim; Arafa, Ibrahim (Arab Journal for Sciences and Research Publishing, 2015)
The objective of this work is: Asses the potential benefit of antioxidant supplementation on the occurrence of preeclampsia at high risk women. Patients and Methods: The number of primigravida women's collected was "294" with gestational age ranged from 18-22 wks. .from (294) prim gravida cases ,(25) women were identified as being at increased risk of pre-eclampsia by abnormal Doppler wave form in either uterine artery at 18-22 weeks' gestation ( defined as a resistance index < 95th centile for gestation or the presence of an early diastolic notch ) , Another (25) women with history in the preceding pregnancy of pre-eclampsia, eclampsia or HELLP (Hemolysis, elevated liver enzymes, low platelets ) . -Total number of eligible participants were, (50) cases. Design and procedure: Cases divided randomly into two groups each 25 cases one group received tablets of 1000 mg vitamin C, (Cevitil efferecent. EPICO) + 400 iu of vitamin E (E-Viton 400 pharco). Venous blood for measurement of PAI-1 and PAI-2, the primary outcome measure was the ratio PAI-1 / PAI-2 and the secondary outcome prospectively according to guidelines of international society for the study of hypertension in pregnancy. Results: Doppler screening was done on, 294 prim gravidae with gestational age ranged from 18-22 weeks; only 42 women showed abnormal Doppler study so asked to come for rescanning at 24 weeks' gestation. 31 out of 42 patients (75%) have persistent abnormal study. The remainders of the 42 women (25%) were withdrawn from the study at 24 wks.' gestation because they have normal uterine-artery scan. Development of mild preeclampsia was statistically lower (p
Keywords: Antioxidant; Occurrence; Pre-eclampsia; Increased Risk